Efisiensi Reproduksi Induk Sapi Bali yang dikawinkan dengan Bangsa Sapi Brangus secara Inseminasi Buatan di Kecamatan Insana Barat Kabupaten Timor Tengah Utara - Alexander Manhitu; Paulus K. Tahuk; Theresia I. Purwantiningsih (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2020)
This Study aims to determine the reproductive efficiency of Bali cows mated with Brangus cows by artificial Insemination (AI) in west Insana District, Nort central Timor Regency. This research will be conducted for two months in the area of west Insana Sub-district, east Central Timor district in July 2019 until September 2019. The method used in this research in the census method carried out on female Bali cows that have been in the IB at least once pregnant and / or have given birth, using the semen of the Brangus male (sample). Primary data were interviews and observations (guided by prepared questionnaires) with a number of breeders who have a Balinese cow with a minimum of 2 cows. Where as secondary data was obtained from various agencies related to this study such as the livestock service, sub-district monoraphs, and the central statistical office. Conclude that the averange Bali cows mated by AI with semen of Brangus bull males provide good reproductive efficiency and above normal with the values of each variable being: CR: 68,70± 26,83%; S/C: 1,73± 0,79; Long gestation: 272,23 ± 3,96 days CI: 384,62 ± 48,41 days. Reproductive efficiency of Bali cows mated with semen of Brangus male cows has a close ralation ship with: Service per Conception, Conception Rate, Calving Intrval, and Long Gestation.